POTENSI OBYEK DAN DAYA TARIK PULAU PONTIYANAK SEBAGAI WISATA ALAM DI KECAMATAN JAWAI SELATAN KABUPATEN SAMBAS (Potential Object and Attraction as nature Pontiyanak Island in District of South Jawai Regency Of Sambas) - Wati, Hade Irma; rizal, Fah; Idham, M. (JURNAL HUTAN LESTARI, 2015)
ABSTRACT South Jawai is one of the districts that are in regency of Sambas West Kalimantan province. In the district of South Jawai there is a potential for nature tourism is not yet widely known by the public, the potential is in the hamlet Ramayadi, nature tourism potential of the region, namely the Pontiyanak Island, nature tourism potential Pontiyanak Island has a fascinating natural scenery to visit and still have fresh air and natural, but until now there is no relevant agencies interested in developing the site as a tourist attraction, due to the lack of specific information about the tourism potential Pontiyanak Island in detail. The aim of this study was to obtain data on the potential tourist attraction and provide an assessment of the potential attractiveness Pontiyanak Island in regency of Sambas. The method used in this study is a scoring method based on the assessment standards Object to Visit Nature PHKA 2003. Data collection techniques used questionnaires and direct observations in the field. The results showed an average total score of 785.62, from the results obtained in the area of the PontiyanakÂ  island of get the value (A) which means Pontiyanak Island neighborhood potential to be developed as a place or natural attractions. Keywords: Potential tourism, ecotourism, South Jawai, Pontiyanak Island